Anti-Tubular Basement Membrane Antibody Nephritis Manifesting in a Patient With Chronic Lymphocytic Leukemia: A Very Rare Case Report - Niloufar Ebrahimi MD; Behzad Najafian MD; Yan Chen Wongworawat MD; Sayna Norouzi MD; Amir Abdipour MD (SAGE Publishing, 2024)
Anti-tubular basement membrane (anti-TBM) antibody nephritis is a rare type of tubulointerstitial nephritis associated with progressive decline in kidney function. It is characterized histopathologically by tubular atrophy and dilation, interstitial fibrosis, lymphocyte and macrophage-predominant cellular infiltration, and linear deposition of IgG and complement along the tubular basement membrane. We herein present a case of a 69-year-old male who was recently diagnosed with chronic lymphocytic leukemia (CLL) and was referred for evaluation of kidney failure, ultimately diagnosed as anti-TBM antibody nephritis progressing into end-stage kidney disease (ESKD). This case report highlights the management challenges of anti-TBM antibody nephritis as a rare kidney disorder.